1997
DOI: 10.1046/j.1365-2362.1997.670617.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of metoprolol treatment on insulin sensitivity and diurnal plasma hormone levels in hypertensive subjects

Abstract: Abstract.To evaluate the effect of metoprolol on insulin sensitivity and diurnal plasma hormone levels, seven mildly hypertensive subjects were investigated (four men and three women, age 52 Ϯ 8, body mass index 25 . 4 Ϯ 1 . 9, mean Ϯ SD). The study had a placebo-controlled, double-blind, crossover design with 6 weeks' metoprolol treatment (100 mg b.i.d) vs. placebo. At the end of each treatment period 24-h blood samples were collected continuously for diurnal analysis of hormone levels and a hyperinsulinaemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…12,32 The GEMINI and COMET studies found that metoprolol adversely affected glucose metabolism, but carvedilol had neutral metabolic effects. 8,9 A recent review showed that carvedilol did not adversely affect plasma lipids compared to β1-selective agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,32 The GEMINI and COMET studies found that metoprolol adversely affected glucose metabolism, but carvedilol had neutral metabolic effects. 8,9 A recent review showed that carvedilol did not adversely affect plasma lipids compared to β1-selective agents.…”
Section: Discussionmentioning
confidence: 99%
“…12-14 Stimulation of the β2-AR also mediates hepatic glycogenolysis and lipolysis in adipose tissues. 15 Selective (β1) blockade by conventional βblockers, such as metoprolol, leads to unopposed α1-mediated vasoconstriction, thereby reducing blood flow to muscles and glucose uptake in peripheral tissues.…”
Section: Introductionmentioning
confidence: 99%
“…18 Beta blockers also interfere with β2 mediated pancreatic insulin release. 3,19,20 Additionally, reduced insulin release and blockade of hepatic β2 adrenergic receptors elevates glucose production following meals. 4 Beta-blockers have also been shown to increase weight, 21 which is associated with development of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Beta-blockers may negatively affect glucose homeostasis through increased hepatic glucose production, blockade of insulin release, and may worsen insulin resistance through reduced peripheral glucose ulitization. 3,4 The effect of angiotensin converting enzyme (ACE) inhibitors on diabetes risk has been more varied. Post-hoc analyses in large trials originally suggested that ACE inhibition might delay or prevent the onset of DM, 2,5,6 while the DREAM trial did not show a benefit on frank development of diabetes, although did show some improvement in glycemic control with ACE inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Adverse effects of blockade of ß 2 ‐receptors on glucose metabolism have been recognized and repeatedly described [31, 32]. In contrast to unselective betablockers, ß 1 ‐selective blockers appear to be without relevant influence on glucose metabolism [32–35]. However, in some studies adverse effects of ß 1 ‐selective betablockers have been described [36].…”
Section: Do Betablockers Have Adverse Effect On Blood Glucose Metabolmentioning
confidence: 99%